Pre-service teachers’ empathy and attitudes toward inclusive education—The chain mediating role of teaching motivation and inclusive education efficacy - Nana Jiang; Haijun Li; Soon-Yew Ju; Lai-Kuan Kong; Jing Li (PLoS ONE, 2025)
Recently, inclusive education has become the direction of special education development. Inclusive education requires that teachers’ educational philosophies and approaches meet the needs of all students. Since pre-service teachers are future educators in training, it is vital to investigate their perspectives on inclusive education. Pre-service teachers’ attitudes, ability and views of inclusive education have an impact on the success of inclusive education practice. However, little literature has examined the influence of psychological mechanism of pre-service teachers toward inclusive education, i.e., the impact of empathy on pre-service teachers’ attitudes toward inclusive education and the mediating effects of teaching motivation and inclusive education efficacy toward the aforementioned relationship. Thus, this study employed Stimulus-Organism-Response’s (S-O-R) model to underpin the research framework that examines the relationship between pre-service teachers’ empathy and attitudes toward inclusive education and the mediating effects of teaching motivation and inclusive education efficacy in the Chinese context. Quantitative data through survey questionnaires was collected from 480 Chinese pre-service teachers and analysed using PLS-SEM. Findings suggested that pre-service teachers’ empathy directly predicted teaching motivation, inclusive education efficacy, and attitudes toward inclusive education. Teaching motivation and inclusive education efficacy together play a chain mediating role in the relationship between empathy and pre-service teachers’ attitudes toward inclusive education. The results of this study offer a theoretical framework that explains in detail the psychological mechanisms underlying the effects of pre-service teachers’ empathy, teaching motivation, and inclusive education efficacy on attitudes towards inclusive education. The research findings also provide practical guidance for the professional development of teachers, talent cultivation, and the development of inclusive education in higher education.